ANALISIS PERAN POKDARWIS DALAM PENGEMBANGAN DESA WISATA TERPADU PULAU BELAKANG PADANG - Maldin, Siska Amelia (Puslitabmas Batam Tourism Polytecnic, 2022)
This research is intended to describe community empowerment through Pokdarwis to develop an integrated tourism village on Pulau Belakang Padang, Batam City. Data collection in this study were carried out by observation, interviews, and literature study. The results of this study are to provide an overview of the potential concepts that can be developed for the Pulau Belakang Padang Tourism Village.